2006
DOI: 10.1089/cpb.2006.9.297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excessive Internet Use on Undergraduate Students in Pakistan

Abstract: This study was undertaken to investigate the positive and negative effects of excessive Internet use on undergraduate students. The Internet Effect Scale (IES), especially constructed by the authors to determine these effects, consisted of seven dimensions namely: behavioral problems, interpersonal problems, educational problems, psychological problems, physical problems, Internet abuse, and positive effects. The sample consisted of 200 undergraduate students studying at the GC University Lahore, Pakistan. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 16 publications
4
87
1
9
Order By: Relevance
“…According to Yüksel and Yılmaz (2016), the reason why there is a negative correlation between Internet addiction levels and problem-solving skills is the fact that, when dependency increases, problem-solving skills are negatively affected in turn. It has also been claimed by Kelleci (2008) that Internet dependency negatively affects social relations and feelings (Engelberg and Sjoberg, 2004), along with various skills that require personal development and communication skills, such as selfexpression (Suhail & Bargees, 2006). For teachers, the differences in communication skills have a negative impact on both academic and other tasks.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to Yüksel and Yılmaz (2016), the reason why there is a negative correlation between Internet addiction levels and problem-solving skills is the fact that, when dependency increases, problem-solving skills are negatively affected in turn. It has also been claimed by Kelleci (2008) that Internet dependency negatively affects social relations and feelings (Engelberg and Sjoberg, 2004), along with various skills that require personal development and communication skills, such as selfexpression (Suhail & Bargees, 2006). For teachers, the differences in communication skills have a negative impact on both academic and other tasks.…”
Section: Discussionmentioning
confidence: 97%
“…One study found that physical competences of users increased in one year when their Internet usage time was reduced (Larwin & Larwin, 2008). Psychosomatic symptoms, such as a lack of physical energy, physiological Volume 10 Number 4 2017 dysfunction and weak immunity (Cao, et al, 2011), caused by computer use for long hours, result from using the Internet for a long period of time in an inappropriate sitting position (Shields & Behrman, 2000), the formation of carpet tunnel syndrome in muscle groups (Shields & Behrman, 2000), the formation of health problems in the eyes, such as eye fatigue and eye irritation due to staring at a monitor for protracted periods (Subrahmanyam et al, 2000;Healy, et al, 2010), and increases in migraine pain (Suhail & Bargees, 2006) also negatively affect the individual in psychological and social terms, resulting in low self-esteem and the occurrence of occupational and personal disorders.…”
Section: Relationship Between Internet Addiction and Problem-solving mentioning
confidence: 99%
“…Berbagai penelitian mengenai PIU telah dilakukan sebelumnya pada mahasiswa di berbagai negara seperti Pakistan (Suhail & Bargess, 2006), Turkey (Özcan & Buzlu, 2007), Taiwan (Chen & Peng, 2008), dan USA -Cina (Zhang, Amos, & McDowell, 2008), akan tetapi tidak banyak publikasi mengenai fenomena PIU pada mahasiswa di Indonesia. Penelitian ini diharapkan mampu menjadi sumber acuan demi pengembangan ilmu psikologi, khususnya cyberpsychology serta memperkaya pemahaman mengenai PIU pada mahasiswa di Indonesia.…”
unclassified
“…A number of studies indicate a significant correlation between the amount of time spent surfing the Internet and the risk of developing Internet addiction amongst American college students, Chinese, Taiwanese, Internet users from Pakistan, and Australian students (Brenner, 1997;Liang, 2003;Lin & Tsai, 2002;Suhail & Bargees, 2006;Wang, 2001). …”
Section: ! Law 3 -Medium With Time Dimension Determines Its Usage Lengthmentioning
confidence: 99%